Prevalence and molecular variance of human papillomavirus among women in Kota Kinabalu, Sabah, Malaysia - Nur Ezzah Sainei (2019)
Human papillomavirus (HPV) is regarded as one of the influential causes of cervical cancer incidences worldwide. Information concerning the geographical distribution of HPV genotypes is now considered as crucial in order to determine the efficacy of HPV vaccine protection against infections of diverse types of HPV. Studies of HPV genotype distribution along with its association with various risk factors and the nature of its carcinogenicity based on the established lineages are still at a juvenile stage in Malaysia with a lack of data particularly among the population in Sabah. A total of 240 samples were successfully collected from female volunteers who were recruited from Sabah Women and Children Hospital as well as UMS Polyclinics Kingfisher in a period of 12 months. HPV was detected by means of polymerase chain reaction (PCR) amplification of Ll gene from HPV viral genome using primer pair MY09/MY11. Then, HPV genotyping was performed by subjecting the PCR products to an established restriction fragment length polymorphism (RFLP) procedure which was able to detect 49 mucosa! HPV genotypes. All data concerning participants' sociodemographic, clinical, and behavioural characteristics were acquired from the questionnaires which were provided to the women along with informed consent forms. Toe results of Pap smear test were obtained from gynaecologists in charge. Approximately 13 primer pairs were designed based on the regions of LCR and E6 gene of each HPV genotype detected. PCR amplification was conducted using the designed primers and all PCR products were purified and sequenced. Analyses of sequence variation of each HPV isolate was performed by comparing the acquired sequences to the prototype sequences obtained from GenBank. Meanwhile, multiple alignment was performed on all acquired sequences and their prototypes, and neighbour-joining (NJ) phylogenetic trees were generated along with 1000 bootstrap replicates in order to evaluate their reliability. Toe prevalence of HPV infection among the 240 women residing in Kata Kinabalu was 9.6%. A total of 13 HPV genotypes were discovered whereby HPV-56 (high-risk) and HPV-70 (probable high-risk) were among the most prevalent types identified. HPV-56 was also found to associate with low-grade neoplasia (LSIL). Univariate and multivariable models were used to analyse the strength of relationship between risk factors and HPV infection. Toe results of the analyses indicated a significant association between HPV infection and two risk factors: education (OR: 0.13, 95% CI: 0.03-0.62) and employment (OR: 4.94, 95% CI: 1.58-15.40). Toe LCR regions and E6 genes of the 13 HPV genotypes were then amplified and sequenced. Toe analyses of sequence variation and construction of phylogenetic trees indicated that at least four highly oncogenic lineages were found among high-risk HPV variants identified in the study namely HPV-16 A4 (Asian), HPV-33 Al, HPV-56 B, and HPV-58 A, respectively. These four lineages are highly associated with incremental risk of severe cytological lesions of the cervix and development of cervical cancer. Toe outcomes of the study served as a significant baseline information crucial for the women population of Sabah. Toe high prevalence of HPV-56 among women in Sabah indicated that a new strategy of HPV vaccination with next generation of vaccine targeting HPV-56 will be necessary in the future.